Aktivitas Penyembuhan Luka oleh Gel Fraksi Etil Asetat Rimpang Kunyit pada Mencit Hiperglikemik (WOUND HEALING ACTIVITY OF AETHYL ACETATE OF CURCUMA LONGA GEL IN HYPERGLYCEMIC MICE) - Wientarsih, Ietje; Winarsih, Wiwin; Sutardi, Lina Noviyanti (Jurnal Veteriner, 2013)
Traditional remedies generally use plant based therapies for treatments. The availability of plantfor treatments is relatively abundant in Indonesia, whether as treatments for diabetic wounds or antiinflammation. Curcuma longa Linn has been reported as an alternative treatment for several diseasesincluding wound healing. The aim of this study was to investigate the possible effect on wound healing ofethyl acetate of C.longa gel in skin hyperglycemic mice. The ethyl acetate of C.longa gel was evaluated toassess its healing efficiency on excision wound. Thirty mice were used in this study. The mice were dividedinto three groups i.e.: KN as a negative control (without treatment), KP as a positive control (Neomycinsulfate), and treated groups (GE= ethyl acetate gel). There was a significant effect on histopathologicalcharacteristics in wound healing of treated mice with ethyl acetate gel compared with KN mice. It seemthat C.longa gel is a potential for phyto-therapeutic agent in management of wound healing.
Keywords: C. longa, gel, wound, hyperglycemic